2018
DOI: 10.1063/1.5022875
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar SnOx thin-film transistors achieved at high sputtering power

Abstract: In this work, ambipolar behavior was observed in SnOx TFTs fabricated at a high sputtering power of 200 W and post-annealed at 150-250 o C in ambient air. X-raydiffraction patterns show polycrystallisation of SnO and Sn in the annealed SnOx films. Scanning-electron-microscopy images revealed that microgrooves occurred after the films were annealed. Clusters subsequently segregated along the microgrooves, and our experiments suggested that they are most likely Sn clusters. Atomic-force-microscopy images indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
(28 reference statements)
0
13
0
2
Order By: Relevance
“…After the evaporation of gate metal (Ni/Au), the AlGaN/ GaN HEMTs with p-SnO gate cap were fabricated. Particularly, the room-temperature sputtering and low-temperature air annealing method for p-SnO, proposed in our previous work [45], is perfectly compatible to the fabrication of GaN-based HEMTs. In addition, the metal gate HEMT has also been fabricated except for the p-SnO cap deposition, and the corresponding electrical properties can be found in Fig.…”
Section: Experimental Verification Of P-sno Gate Cap Hemtmentioning
confidence: 92%
“…After the evaporation of gate metal (Ni/Au), the AlGaN/ GaN HEMTs with p-SnO gate cap were fabricated. Particularly, the room-temperature sputtering and low-temperature air annealing method for p-SnO, proposed in our previous work [45], is perfectly compatible to the fabrication of GaN-based HEMTs. In addition, the metal gate HEMT has also been fabricated except for the p-SnO cap deposition, and the corresponding electrical properties can be found in Fig.…”
Section: Experimental Verification Of P-sno Gate Cap Hemtmentioning
confidence: 92%
“…SnO has also been known as the only oxide material that exhibits an ambipolar behavior, and there are many reports of this ambipolar behavior in SnO TFTs. [54][55][56][57][58] Luo et al showed the importance of back-channel surface of SnO on its ambipolar behavior, which demonstrated that the chemical passivation effectively reduces the subgap states and thereby enables the facile shift of Fermi-level by the applied gate voltage, achieving the ambipolar behavior in the SnO TFTs. [54] Similarly, Lee et al investigated the switching mechanism of SnO TFTs by performing back-channel defect engineering.…”
Section: Critical Issuesmentioning
confidence: 99%
“…One of them is performed by creating Sn vacancies, which can introduce a hole carrier to the valence band of SnO 2 , commonly attained by controlled sputtering method deposition. [ 14 ] The other way is by chemical doping with group IIIA elements such as indium (In) and gallium (Ga), which can occupy an Sn site in the SnO 2 lattice. [ 15 ] Based on those earlier reports, we have fabricated a SnO 2 TFT by choosing LiInO 2 and LiGaO 2 as ion‐conducting oxide dielectrics, which can dope In and Ga atoms, respectively, to the interfacial layer of SnO 2 .…”
Section: Figurementioning
confidence: 99%
“…One of them is to create Sn vacancies which can introduce hole carrier to the valance band of SnO 2 which is commonly achieved by sputtering method deposition. [36][37][38] The other way is by chemical doping with group IIIA elements like indium (In), gallium (Ga) which can occupy a Sn site in the SnO 2 lattice. [39][40][41][42] Based on those earlier reports, we have fabricated SnO 2 TFT by choosing two ion-conducting oxide dielectrics that can introduce p-doping to the dielectric/semiconductor interface to enhanced hole conduction of SnO 2 .…”
Section: Introductionmentioning
confidence: 99%